2007
DOI: 10.1071/sh06070
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of intergenerational sexual relationships: the experience of schoolgirls in Botswana

Abstract: Effective policy and practice can be informed by the findings, leading to a reduction in HIV transmission as a result of intergenerational sex. In particular, the study has drawn attention to girls who are able to assert themselves within intergenerational sexual relationships and successfully negotiate safe sex. These strategies can be incorporated in programs to assist girls who face challenges and difficulties in negotiating safe sex with older men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 17 publications
1
39
1
1
Order By: Relevance
“…For older women, negotiation of condom use is nearly inconceivable in the context of sexual relations. For younger women, difficulty in condom use has been associated with risk perception 45,46 , cultural issues 47 , and difficulty in negotiation of use with older partners 30,48,49,50,51,52 , where the smaller the difference in age, the higher the adherence to condom use. And although there are indications that women who have sex with older men are less inclined to use contraceptive methods 27 , further research is needed on the sexual and reproductive health of women in these relations and how gender inequality issues appear in this context.…”
Section: Discussionmentioning
confidence: 99%
“…For older women, negotiation of condom use is nearly inconceivable in the context of sexual relations. For younger women, difficulty in condom use has been associated with risk perception 45,46 , cultural issues 47 , and difficulty in negotiation of use with older partners 30,48,49,50,51,52 , where the smaller the difference in age, the higher the adherence to condom use. And although there are indications that women who have sex with older men are less inclined to use contraceptive methods 27 , further research is needed on the sexual and reproductive health of women in these relations and how gender inequality issues appear in this context.…”
Section: Discussionmentioning
confidence: 99%
“…While such factors may be at play in many intergenerational partnerships, exceptions do exist. Nkosana and Rosenthal's qualitative research showed that some relationship between young girls and older men were associated with desire for pleasure, enjoyment and sense of equal partnership by the younger partner (34). However, young women involved in such kind of relationship may fail to appreciate the precarious nature of such relationships.…”
Section: Intergenerational Sexmentioning
confidence: 99%
“…A study in Kenya reported that orphaned children sought out older partners in order to replace a parental figure, or to provide them with emotional support, affection and attention which was lacking in foster homes (Longfield et al 2004). A qualitative study in Botswana among young girls with sugar daddies shows associated limitations on the girls' capacity to negotiate safe sex (Nkosana and Rosenthal 2007).…”
Section: Older Sexual Partners Sugar Daddies and Sugar Mummiesmentioning
confidence: 99%